Review time of oncology drugs and its underlying factors: an exploration in China - Zhu, Xingyue; Liu, Bao (Frontiers in Pharmacology, 2023)
How the launch delay of drug and other factors of interest can influence the length of review period by drug agencies is still unknown, and understanding this can help better strike the trade-off related to review speed. We included all new oncology drug applications submitted to China National Medical Product Administration (NMPA) between January 1, 2018, and December 31, 2021, and ultimately succeeded in achieving marketing approval. For each drug, the length of the NMPA review process and other major characteristics were collected, including registration class, approval class, priority review designation, launch delay relative to the United States, as well as the number of patients enrolled, comparator, and primary endpoint of the pivotal trials supporting the approval. From 2018 to 2021, the NMPA received 137 oncology applications that were ultimately approved. Half of the approvals (76[55.5%]) were first licensed in the US, leaving a median launch delay of 2.71 years (IQR, 1.03-5.59) in China. In the pivotal studies, the median enrollment was 361 participants (IQR, 131-682), and the use of control groups (90[65.7%]) and surrogate endpoints (101[73.7%]) was prevalent. The median review times was 304 days (IQR, 253-376). Multivariate analysis for log-transformed review times showed that, larger enrollment (>92) was associated with a drop of 20.55% in review times (coefficient=-0.230; 95% CI, -0.404 to -0.055; P=0.010); and a short delay (0-1.95 years) was associated with a drop of 17.63% in review times (coefficient=-0.194; 95% CI, -0.325 to -0.062; P=0.004). The short launch delay relative to the US was one important driver to the review speed of the NMPA, which might suggest its latent regulatory reliance on the other global regulator during the post-marketing period when new information on the drug’s clinical benefit was still lacking.